Unfolding the Flypaper : The Effects of Intergovernmental Grants in an Open Local Economy. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 1989)
Empirical studies of the effects of intergovernmental grants to localities do not support standard microeconomic predictions. Block grants have surprisingly large positive effects on public expenditures. Researchers have attributed this 'flypaper effect' to imperfect information (fiscal illusion), bureaucratic self-interest (Leviathan motives), and flawed econometrics. In this paper, a three-sector, computable general equilibrium model of a local economy is used to explore the effects of block grants and matching grants. The paper demonstrates that without fiscal illusion or unresponsive bureaucrats, these grants can have large spending consequences. Fiscal adjustments, mobility, and capitalization effects explain the leveraged impact of intergovernmental grants.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet